HVAC engineer's handbook - Porges, F. (Fred)
In the almost sixty years since the publication of the first edition of HVAC Engineer's Handbook, it has become widely known as a highly useful and definitive reference for HVAC engineers and technicians alike, and those working on domestic hot and cold water services, gas supply and steam services. The 11th edition continues in the tradition of previous editions, being easily transportable and therefore an integral part of the HVAC engineer or technician's daily tools. Newly updated data on natural ventilation, ventilation rates, free cooling and night-time cooling, make the 11th edition of the HVAC Engineer's Handbook a vital source of information. Fred Porges has worked in both the manufacturing and process industries, and became a partner in a building services consultancy in 1962. He has held senior positions with design contractors, and his experience covers every building service and type of building from schools to housing, factories to laboratories. * Provides comprehensive data in compact form for ease of use * Keep up to date with a full comparative summary of all air conditioning techniques * Provides you with must-have information for dealing with HVAC.